Current aspects of project management in a corporation - Khilukha, Oksana (Odessa : Odessa National Economic University, 2025)
The purpose of this study is to conduct a comprehensive analysis of project management practices under conditions of limited resources, with a focus on optimizing time, cost, and quality. Special attention is given to the application of network diagrams as tools for effective scheduling and resource allocation. The research is based on a systems approach, comparative analysis methods, synthesis of practical experience, and examination of interdependencies between scheduling and critical project success factors. Empirical data and case studies are used to validate proposed solutions. The study identifies major challenges related to inefficient project management within traditional organizational structures, such as a lack of alignment between strategic goals and project execution. It proposes practical recommendations for improving resource distribution mechanisms, enhancing flexibility in scheduling, and ensuring stronger integration of project management with corporate strategy. The use of network diagrams allows for the identification of critical operations and optimization of project timelines through resource leveling and activity splitting techniques. This research highlights underexplored aspects of project management—specifically, the dynamic interplay between limited-resource scheduling and critical path flexibility. The novelty lies in the proposed framework that combines adaptive planning techniques with strategic alignment and real-time risk management. It also addresses organizational challenges related to authority distribution and cross-functional coordination in matrix structures. The findings are valuable for enterprises aiming to increase project efficiency in environments with constrained resources and high demand for timely and cost-effective results. The proposed approaches and tools, including network-based planning and resource optimization, can be applied across various industries to improve the success rate of both internal and external projects. Future research should focus on developing advanced decision-support systems that leverage real-time data analytics.
Keywords: corporation; project management; network diagram; scheduling; limited resources; critical path.